Anticancer and cancer preventive activities of shogaol and curcumin from Zingiberaceae family plants in KG-1a leukemic stem cells - Pawaret Panyajai; Natsima Viriyaadhammaa; Sawitree Chiampanichayakul; Yasuhisa Sakamoto; Siriporn Okonogi; Toshiro Moroishi; Songyot Anuchapreeda (BMC Complementary Medicine and Therapies)
Abstract Background Leukemic stem cells (LSCs) present a significant challenge in the treatment of leukemia in patients because they exhibit a drug-resistant phenotype, making them difficult to eliminate. Searching for a new anticancer drug is crucial for improving leukemia treatment. Plants from the Zingiberaceae family are frequently used in traditional medicines due to their safety and accessibility. This study explores the anticancer activity, cancer preventive properties, and apoptosis inducing mechanisms of active compounds derived from these plants. Methods Ten crude ethanolic extracts from each plant of the Zingiberaceae family were obtained using maceration techniques. The cytotoxicity of all extracts anticancer was assessed in comparison to anticancer drugs (cyclophosphamide, cytarabine, doxorubicin, and idarubicin) using MTT assay on cancer cell lines (KG-1a, K562, A549, MCF-7, and HeLa) and peripheral blood mononuclear cells (PBMCs). Cancer prevention properties of the effective extracts and their active compounds were evaluated by measuring the levels of tumor necrosis factor-alpha (TNF-α), interleukin-2 (IL-2), and nitric oxide (NO) using commercial kits. Cell cycle and cell death analyses were conducted using flow cytometry. Moreover, the effects of effective extracts and their active compounds on WT1 and CD34 expressions, as well as the apoptosis mechanism induced by the active compounds in KG-1a cells, were determined by Western blotting. Results The cytotoxicity tests revealed that crude ethanolic extracts from Curcuma longa, C. zedoaria, and Zingiber officinale exhibited effective cytotoxicity against cancer cell lines while demonstrating lower impact on PBMCs. The active compounds of C. longa and C. zedoaria are curcuminoids, while those in Z. officinale are shogaol and gingerol. Notably, the IC20 values of curcuminoids and shogaol exhibited cancer prevention properties and reduced WT1 protein expression, thereby inhibiting cell proliferation. Furthermore, shogaol and curcumin demonstrated the ability to arrest the cell cycle at the G2/M phase and induce apoptosis through the Akt pathway. Conclusion These findings highlight shogaol and curcumin as promising compounds for leukemia treatment.